Potret Keterwakilan Perempuan dalam Wajah Politik Indonesia Perspektif Regulasi dan Implementasi - Hardjaloka, Loura (Jurnal Konstitusi, 2012)
In Article 28C paragraph (2) of the Constitution 1945, “Every person is entitled to advance himself in the fight for their rights to collectively build a community, nation and country”, Article 28D paragraph (3) which reads, “Every citizen is entitled to equal opportunities in government”, should be the basis for guaranteed political rights of women. However, parties often overlook the urgency of this women’s representation. In addition to the provisions of the 1945 Constitution, there is also Election Law, Article 7 and Article 8 of CEDAW and the Convention on the Political Rights of Women who all voiced that women have equal political rights with men. But will the urgency of women’s representation in politics is hampered due to negative stereotypes of women’s  capabilities.